Policy problems and policy design - Peters, B Guy (Cheltenham, UK Edward Elgar, 2018)
B. Guy Peters presents a critique of conventional policy design methods, placing emphasis on the need to formulate interconnecting designs for issues that cross multiple policy areas. He advocates the use of analytic categories for understanding problems rather than functional categories, such as defence and health, to change the perspective of problems and modernize policy design.

Whereas previous literature takes a top-down, technocratic approach, this new perspective emphasizes the importance of context and the pressing need to unite designs between policy areas. Effective methods should be open and inclusive by reviewing a wider range of policy alternatives. Chapters discuss the logic of policy design, the different problems that can arise in policy and how to link these issues with the correct policy instruments successfully. Peters also provides a set of ten key principles that can be used to improve the technique of policy formulation for effective and realistic designs.

For any academic, researcher or student of public policy interested in the formulation of policy decisions, this book will be an essential tool for successful policy analysis. Current policymakers and strategists will benefit from the in-depth discussion on tackling policy problems as well as improving and interconnecting policy designs.
Contents: Preface 1. The Logic of Policy Design 2. The Problem of Policy Problems 3. Wicked, Complex or Just Difficult Problems 4. Linking Policy Problems and Policy Instruments 5. The “New” Policy Design 6. Conclusion: Toward Better Policy Design References Index
Includes bibliographical references and index
Keywords: Policy sciences